Journal of Homeland Security and Emergency Management (De Gruyter, 2004)
The Journal of Homeland Security and Emergency Management (JHSEM) publishes original, innovative and timely articles describing and assessing research and practice in the fields of homeland security and emergency management. JHSEM promotes a comprehensive and dynamic perspective, providing readers with up-to-date information regarding the evolving nature of the homeland security and emergency management fields.